Integrating the four basic language skills through children tales - Gallegos, María de Lourdes; Loja, Yadira
Learning a new language for children is a process that involves some difficulties, among these, we have the restricted span of attention that pupils have during the teaching- learning process. This study used tales to overcome this problem. It integrated the four basics skills and its sub-skills considering individual characteristics and children´s age. To use children tales to teach children can contribute to the acquisition of a new language because through it teachers can develop a variety of activities that develop all the skills. Also, tales can create a good environment which benefits teachers and students to learn something important for their real lives.